Honokiol inhibits sphere formation and xenograft growth of oral cancer side population cells accompanied with JAK/STAT signaling pathway suppression and apoptosis induction. Issue 1 (December 2016) - Huang, Jhy-Shrian; Yao, Chih-Jung; Chuang, Shuang-En; Yeh, Chi-Tai; Lee, Liang-Ming; Chen, Ruei-Ming; Chao, Wan-Ju; Whang-Peng, Jacqueline; Lai, Gi-Ming
Abstract Background Eliminating cancer stem cells (CSCs) has been suggested for prevention of tumor recurrence and metastasis. Honokiol, an active compound ofMagnolia officinalis, had been proposed to be a potential candidate drug for cancer treatment. We explored its effects on the elimination of oral CSCs both in vitro and in vivo. Methods By using the Hoechst side population (SP) technique, CSCs-like SP cells were isolated from human oral squamous cell carcinoma (OSCC) cell lines, SAS and OECM-1. Effects of honokiol on the apoptosis and signaling pathways of SP-derived spheres were examined by Annexin V/Propidium iodide staining and Western blotting, respectively. The in vivo effectiveness was examined by xenograft mouse model and immunohistochemical tissue staining. Results The SP cells possessed higher stemness marker expression (ABCG2, Ep-CAM, Oct-4 andNestin ), clonogenicity, sphere formation capacity as well as tumorigenicity when compared to the parental cells. Treatment of these SP-derived spheres with honokiol resulted in apoptosis induction via Bax/Bcl-2 and caspase-3-dependent pathway. This apoptosis induction was associated with marked suppression of JAK2/STAT3, Akt and Erk signaling pathways in honokiol-treated SAS spheres. Consistent with its effect on JAK2/STAT3 suppression, honokiol also markedly inhibited IL-6-mediated migration of SAS cells. Accordingly, honokiol dose-dependently inhibited the growth of SAS SP xenograft and markedly reduced the immunohistochemical staining of PCNA and endothelial marker CD31 in the xenograft tumor. Conclusions Honokiol suppressed the sphere formation and xenograft growth of oral CSC-like cells in association with apoptosis induction and inhibition of survival/proliferation signaling pathways as well as angiogenesis. These results suggest its potential as an integrative medicine for combating oral cancer through targeting on CSCs.